The Role And Responsibility Of Teachers In The 21st Century - Pristiwiyanto Pristiwiyanto (JOSSE: Journal of Social Science and Economics, 2022)
The teacher is a very important element and cannot be ignored in the teaching and learning process, because the teacher can determine the success or failure of a teaching and learning process. Therefore, in the education and teaching process it is necessary to have qualified teachers, which means that in addition to mastering the subject matter, teaching methods, they also understand the basics of education. The basics of education are very, very important to be known by a teacher in carrying out his noble duties as a teacher or educator, this is a means to arouse and motivate students in their learning process. Although the mastery of the material is very good, but it is not supported by knowledge of didactic factors, it will have the impact of an obstacle in mastering the material for students to what is conveyed by the teacher. Although the learning experience actually makes it easier for teachers to deliver lessons accompanied by the use of good and appropriate methods.